2018 Annual American Control Conference (ACC) 2018
DOI: 10.23919/acc.2018.8431018
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Microgrids in Frequency Regulation Markets

Abstract: Distributed energy resources (DERs) are playing an increasing role in ancillary services for the bulk grid, particularly in frequency regulation. In this paper, we propose a framework for collections of DERs, combined to form microgrids and controlled by aggregators, to participate in frequency regulation markets. Our approach covers both the identification of bids for the market clearing stage and the mechanisms for the real-time allocation of the regulation signal. The proposed framework is hierarchical, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…While distributed control has the potential to enable DER participation in the frequency regulation market (e.g., [4]), there is a general lack of large-scale testing to prove its effectiveness for widespread adoption by system operators. The 2017 National Renewable Energy Laboratory Workshop on Autonomous Energy Grids [5] concluded that "A major limitation in developing new technologies for autonomous energy systems is that there are no large-scale test cases (...).…”
Section: Introductionmentioning
confidence: 99%
“…While distributed control has the potential to enable DER participation in the frequency regulation market (e.g., [4]), there is a general lack of large-scale testing to prove its effectiveness for widespread adoption by system operators. The 2017 National Renewable Energy Laboratory Workshop on Autonomous Energy Grids [5] concluded that "A major limitation in developing new technologies for autonomous energy systems is that there are no large-scale test cases (...).…”
Section: Introductionmentioning
confidence: 99%